Consumers and limitation of the right to the recovery of unjust enrichment - Lajošová, Iveta (Technium Social Sciences Journal, 2023)
The academic thesis analyses some interpretative problems related to the assessment of the beginning of the subjective limitation period in the case of unjust enrichment arising in the context of consumer credit relations. The author interprets the statute of limitations of the right to release of unjust enrichment in the light of the applicable de lege lata legislation, which is supplemented by the current case law. The author presents arguments indicating that the decisions of the Court of Justice of the European Union have not been properly implemented in the decision-making activity of the courts. Using case law, she provides a brief overview of the subject matter relating to unjustified enrichment in consumer law.